2023
DOI: 10.3390/vetsci10020088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Histologic Grade of Digital Squamous Cell Carcinomas in Dogs and Copy Number Variation of KIT Ligand—A Correlation Study

Abstract: Dark-haired dogs are predisposed to the development of digital squamous cell carcinoma (DSCC). This may potentially suggest an underlying genetic predisposition not yet completely elucidated. Some authors have suggested a potential correlation between the number of copies KIT Ligand (KITLG) and the predisposition of dogs to DSCC, containing a higher number of copies in those affected by the neoplasm. In this study, the aim was to evaluate a potential correlation between the number of copies of the KITLG and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A KITLG copy number value >4 was found to be correlated with a predisposition to dSCC in black standard poodles compared with light-coloured standard poodles [ 35 ]. In a recent study, we found that 55 black-coated and black and tan dogs with dSCC had mean copy number values ranging from 5.5 to 5.8 in contrast to four light-coated animals with dSCC that had a mean copy number value of 4.5 [ 16 ]. Interestingly, this study has shown that there is a predictive correlation between higher germline KITLG copy number values and increased histological aggressiveness of digital SCC in dogs (mainly black-coated breeds and black and tan breeds) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A KITLG copy number value >4 was found to be correlated with a predisposition to dSCC in black standard poodles compared with light-coloured standard poodles [ 35 ]. In a recent study, we found that 55 black-coated and black and tan dogs with dSCC had mean copy number values ranging from 5.5 to 5.8 in contrast to four light-coated animals with dSCC that had a mean copy number value of 4.5 [ 16 ]. Interestingly, this study has shown that there is a predictive correlation between higher germline KITLG copy number values and increased histological aggressiveness of digital SCC in dogs (mainly black-coated breeds and black and tan breeds) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dark coat colour is correlated to the development and aggressiveness of squamous cell carcinoma [ 1 , 2 , 3 , 4 , 5 , 6 , 13 , 16 ]. A predisposition for squamous cell carcinoma in standard schnauzers (SS) and giant schnauzers (GS) has been identified by various authors [ 1 , 4 , 5 , 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A copy number variation (CNV) at the KITLG gene is responsible for coat colour intensity [ 27 ]. Furthermore, the CNV at the KITLG gene is associated with the predisposition to digital SCC in black poodles [ 28 ] and black giant schnauzers [ 29 ], as well as with the degree of the digital SCC’s histological aggressiveness [ 30 ]. However, other genetic factors may play a role, suggesting that there are multiple pathways leading to the final oncogenesis of digital SCC [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the literature on digital SCC, there is only one study on 38 cases of digital SCC in schnauzers, which included 12 GSs (32%), 24 SSs (63%), and 2 MSs (5%) [ 31 ]. Most other publications made no distinction of the schnauzer size variants for specific clinical or pathological parameters [ 3 , 9 , 12 , 30 ]. Thus, the aim of the present study is to compare the clinical and macroscopic findings of digital SCC in giant, standard, and miniature schnauzers based on a high number of cases.…”
Section: Introductionmentioning
confidence: 99%